PENGARUH PEMERIKSAAN DAN PELAKSANAAN SELF ASSESMENT SYSTEM TERHADAP TINGKAT KEPATUHAN WAJIB PAJAK PADA KPP MADYA MAKASSAR - Ulfa Rabiyah (AkMen JURNAL ILMIAH, 2015)
Influence of Tax Audit, Self Assessment System and Tax Awareness to Taxpayer Compliance In KPP Madya Makassar. This study aims to identify and analyze the partial effect of Tax Audit, the tax officer service and Tax Awareness to Taxpayer Compliance In KPP Madya Makassar. The variable in this study is the Tax Audit (X1) Self Assessment System (X2) Tax Awareness (X3) and the Taxpayer Compliance (Y). The data used in this research is primary data obtained from the taxpayer through questionnaires and interviews and secondary data obtained from the KPP Madya Makassar closely connected with the study. The analytical method used is multiple linear regression analysis with the help of statistical program SPSS version 16.0. The results showed that the partial of Tax Audit has positive and significant impact on the Taxpayer Compliance, Self Assessment System and significant positive effect on the Taxpayer Compliance and Tax Awareness has positive and significant impact on taxpayer compliance in KPP Madya Makassar.